The Influence of E-Tax System, Digital Literacy, Masculinity Culture, and Social Dilemma on Individual Taxpayer Compliance (WPOP) - Meiniza Hidhayatul Rohma; Rohmad Yuliantoro Catur Wibowo (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2026)
Individual taxpayer compliance is a crucial factor in optimizing state revenue, yet compliance remains a challenge in various regions. This study aims to analyze the impact of the e-tax system, digital literacy, masculinist culture, and social dilemmas on individual taxpayer compliance in Pemalang Regency. This study employed a quantitative approach with a survey method by distributing questionnaires to 107 taxpayer respondents, then analyzed using multiple linear regression. The results showed that all independent variables simultaneously had a significant effect on taxpayer compliance. Partially, the e-tax system, digital literacy, and masculinist culture had no significant effect, while social dilemmas had a significant effect. These findings suggest that social factors and collective awareness are more important determinants of compliance than technological factors. Therefore, the tax authorities need to strengthen educational and social approaches to improve compliance and build public trust in the tax system in a sustainable manner.